2005
DOI: 10.7205/milmed.170.6.516
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Care Provided at an Echelon II Medical Unit during Operation Iraqi Freedom

Abstract: We describe the types of medical problems encountered at a U.S. Army echelon II medical facility during Operation Iraqi Freedom in the period after completion of major ground combat operations, a time of nation restructuring and intermittent, intense, armed conflict. A total of 4,831 patients were assessed between October 1, 2003 and June 30, 2004, 74% with disease and nonbattle injury presentations, 19% with dental complaints, and 7% wounded in action (WIA). Disease and nonbattle injury evaluations were predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 8 publications
2
48
0
3
Order By: Relevance
“…Injuries caused by IEDs result from blast wave-induced changes in atmospheric pressure (primary blast injury), from objects projected from the blasts into people (secondary blast injury), and from people being propelled from the blast (tertiary blast injury) [1][2]. A recent study found that 47 percent of blast-related injuries in Iraq involved the head [3]. Early literature describes a condition in which soldiers coming in contact with powerful explosions were rendered unconscious or dazed when no external injury was noted.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries caused by IEDs result from blast wave-induced changes in atmospheric pressure (primary blast injury), from objects projected from the blasts into people (secondary blast injury), and from people being propelled from the blast (tertiary blast injury) [1][2]. A recent study found that 47 percent of blast-related injuries in Iraq involved the head [3]. Early literature describes a condition in which soldiers coming in contact with powerful explosions were rendered unconscious or dazed when no external injury was noted.…”
Section: Introductionmentioning
confidence: 99%
“…Explosive blast represents a common injury mechanism (Murray et al, 2005;Nelson et al, in press;Owens et al, 2008;Sayer et al, 2008;Wilk et al, 2010), and it appears that combat-related concussion, blast-related concussion (BRC) in particular, may be unprecedented in the current conflicts (Owens et al, 2008;Warden, 2006). Many returning OEF/OIF personnel with concussion histories report cognitive limitations for months or even years post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar Tabla 5. Distribución por autores del mecanismo lesivo empleado [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . de ser conflictos diferentes, presentan gran similitud desde un punto de vista logístico-operativo y asistencial.…”
Section: Guerra En Irak Y Afganistán (2001-actualidad)unclassified
“…Este dato es semejante al obtenido en prácticamente la totalidad de estudios anglosajones que analizan las bajas atendidas en los conflictos más recientes 36-38, 40-42,45-50 . Este hecho también es característico del enfrentamiento entre tropas profesionales e insurgentes, ocurrido en ambiente urbano, desértico o montañoso y en la denominada «guerra asimétrica» [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . Entre otros factores, se puede destacar que las medidas de protección pasiva (blindaje de vehículos, casco y chaleco antifragmentos) y la rápida evacuación hasta una instalación médica, reducen la morbimortalidad en los heridos que han sufrido lesiones por arma de fuego y por explosivos (en inglés Improvised Explosive Device, IED).…”
Section: Guerra En Irak Y Afganistán (2001-actualidad)unclassified